INCIDENCE OF DRY EYE SYNDROME AND OCULAR COMPLAINTS ASSOCIATED WITH CONTACT LENS USE AMONG PRECLINICAL MEDICAL STUDENTS OF THE 2020–2022 COHORT - Fatin Salsabila; Muhammad Asroruddin; Ery Hermawati (jfpublisher, 2026)
Introduction: Dry eye syndrome is a condition that affects the tear film, leading to discomfort, visual disturbances, and tear film abnormalities, which can result in damage to the surface of the eye. One of the causes of dry eyes is the use of contact lenses. This study aims to determine the incidence of dry eye syndrome and eye complaints due to the use of contact lenses in pre-clinical medical students from the 2020-2022 cohort. Methods: This research is an observational analytical study with a cross-sectional approach. A total of 23 selected students were included using total sampling technique. Variables were measured using the Contact Lens Dry Eyes Questionnaire (CLDEQ-8) and Contact Lens Discomfort Index (CLDI), as well as physical examinations including the Schirmer test and Tear Break-up Time (TBUT). Bivariate analysis was performed using Spearman's rho correlation test. Results and Analysis: Seven cases (30.43%) of dry eye were identified. Spearman's rho test revealed statistically significant negative correlations between questionnaire scores and clinical measurements (rs = -0.532 to -0.819, p < 0.05). The negative correlations found indicate that dry eye complaints experienced by contact lens users do not correspond with clinical examination results. This suggests that conventional tear tests are less capable of representing the actual discomfort experienced by contact lens users. Conclusion: The incidence of dry eye and eye complaints due to contact lens use based on the results of the questionnaire and physical examination is 7 people (30.43%).